The Problems and Promises of Japan's Economic-Growth-Led Foreign Policy in Perspective - Hougan, Christian (Tufts Archival Research Center, 2005)
Volume 21, Issue 2. Summer/Fall Japan's post-World War 1I economic strategy has focused predominantly on international trade, but the time has come to change that policy into a more active role in world affairs.